2011
DOI: 10.1128/aac.00957-10
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Amino Acids of Alpha-Melanocyte-Stimulating Hormone Are Requisite for Its Antibacterial Activity against Staphylococcus aureus

Abstract: Alpha-melanocyte-stimulating hormone (␣-MSH) is an endogenous neuropeptide that is known for its anti-inflammatory and antipyretic activities.We recently demonstrated that ␣-MSH possesses staphylocidal activity and causes bacterial membrane damage. To understand the role of its amino acid sequences in the staphylocidal mechanism, in the present study we investigated the antimicrobial activities of different fragments of ␣-MSH, i.e., ␣-MSH(6-13), ␣-MSH(11-13), and ␣-MSH(1-5), and compared them with that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(110 citation statements)
references
References 47 publications
(83 reference statements)
4
105
1
Order By: Relevance
“…We have earlier established the strong antibacterial activity of alpha-melanocyte stimulating hormone (α-MSH) and its congeners containing C-terminal amino acids against both reference and clinical isolates of Staphylococcus aureus ( S. aureus ) [21][23]. Subsequently, we confirmed that the staphylocidal action of α-MSH occurred due to depolarization and permeabilization of the bacterial membrane [22], [23].…”
Section: Introductionmentioning
confidence: 85%
“…We have earlier established the strong antibacterial activity of alpha-melanocyte stimulating hormone (α-MSH) and its congeners containing C-terminal amino acids against both reference and clinical isolates of Staphylococcus aureus ( S. aureus ) [21][23]. Subsequently, we confirmed that the staphylocidal action of α-MSH occurred due to depolarization and permeabilization of the bacterial membrane [22], [23].…”
Section: Introductionmentioning
confidence: 85%
“…After every 5 transfers, evolution of resistance in the positive-selection line against magainin 2 and gramicidin D was identified by determining the MIC in MHB, following NCCLS guidelines (14). Further confirmation of resistance was done by performing a bactericidal assay as described before (15,16).The development of resistance occurred for both of the AMPs studied, as indicated by a gradual rise in MIC values with increasing passage number in the positive-selection lines compared to the MICs in the respective control selection lines. At the 55th passage, the positive-selection strains showed an Ն8-and a 128-fold increase in MIC value for magainin 2 (strain 55MG) and gramicidin D (strain 55GR), respectively, compared to the MIC of the control (Fig.…”
mentioning
confidence: 99%
“…After every 5 transfers, evolution of resistance in the positive-selection line against magainin 2 and gramicidin D was identified by determining the MIC in MHB, following NCCLS guidelines (14). Further confirmation of resistance was done by performing a bactericidal assay as described before (15,16).…”
mentioning
confidence: 99%
“…It is interesting to note that the antimicrobial activity of α -MSH and its C-terminal fragments— α -MSH(6–13) (HFRWGKPV) and α -MSH(11–13) (KPV)—remains intact even in the presence of salts at their physiological concentrations, namely, NaCl (150 mM), CaCl 2 (2 mM), and MgCl 2 (1 mM) [18]. More recently, it has been suggested that α -MSH acts synergistically with antibiotics belonging to different classes.…”
Section: Direct Antimicrobial Activity Of α-Mshmentioning
confidence: 99%